تقييم واقع الصحة الفموية للمرضى المراجعين لقسم طب الفم في كلية طب الأسنان بجامعة تشرين - زريقي سميرة; حيدر علي الشيخ; حمود خالد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 250 مريضاً راجعوا قسم طب الفم في كلية طب الأسنان بجامعة تشرين خلال الفصل الدراسي الأول 2010 – 2011 م، حيث أجري لهم فحصٌ سنيٌ كاملٌ، وفقاً لاستمارةٍ خاصة ومعدة مسبقاً لهذه الدراسة تتضمن عدة متغيرات منها ( الصحة الفموية، الجنس، الشهادة التعليمية ، تفريش الأسنان، استخدام الخيوط السنية). فضلا عن ذلك تم تسجيل عدد الأسنان المنخورة والمرممة والمقلوعة بسبب النخر. هدفت هذه الدراسة إلى تقييم واقع الصحة الفموية لهؤلاء المرضى، وتوفير قاعدة بيانات لهم ورصد الخدمات الطبية السنية المقدمة لهم ومدى الحاجة إلى تقديم خدمات سنية إضافية. كانت نسبة المرضى الذكور 67.2 % من مجموع العينة المدروسة والمرضى الإناث 32.8 %، وكانت أعلى نسبة من بين هؤلاء المرضى بشريحة عمرية تتراوح مابين 20-29 سنة وبنسبة مئوية 47.6 %. بينت الدراسة أن 38.4 % من مجمل المرضى يعانون من صحة فموية سيئة، 65.6 % منهم لا يستخدمون فرشاة الأسنان نهائياً، و 95.2 % من المرضى لا يستخدمون الخيوط السنية. كما بينت الدراسة أن 59.68 % من الأسنان المفحوصة كان مصاباً بآفة نخرية أو تم قلعه نتيجة النخر، مقابل 4.81 % كان مرمماً. This study included 250 patients who consulted the department of oral medicine, Faculty of Dentistry, Tishreen University, during the first term of the educational year 2010-2011. These patients were examined and a full mouth survey was performed according to a pre-established questionnaire. The questionnaire included many variables such as oral health-status, sex, education, teeth brushing, and use of dental floss. In addition to these, decay, restored, and – due to caries - extracted teeth were registered. This study aimed to evaluate the oral health status of the selected patients in order to establish a data base for the patients consulting the department of oral medicine, to control the dental treatments performed to the patients, and to assess the necessity of performing additional dental services. 67.2 % of the patients were males and 32.8 % were females. Most of the patients (47.6 %) were of the age group 20-29 years. The results show that 38.4 % of the patients have a bad oral health, 65.6 % of the patients do not brush their teeth and 95.2 % do not floss their teeth. The study shows that 59.68 % of the examined teeth were decayed or extracted due to caries, whereas 4.81 % were restored.